A Modified Hydrolysis Method of Decolorizing Reactive-Dyed Polycotton Waste Fabric and Extraction of Terephthalic Acid: A Perspective to Reduce Textile Solid Waste - S. S. Nahar; M. S. Rahaman; R. Samadder; F. R. Shagor; R. K. Chadni; M. S. Rahaman; Mubarak A. Khan (Advances in Polymer Technology)
To manage the polycotton textile-waste fabric (PCWF), a modified alkaline hydrolysis method is used for decolorization and separation of polyester as terephthalic acid (TPA). The effects of optimum conditions on TPA yield (%) have been determined to be 97.66±1.94%. Dye degradations and K/S values are measured by UV-visible spectrophotometer. K/S value of PCWF is 37.06 and separated cotton fabric (SCF) is 0.035, respectively. The chemical functionalities and crystallinity of PCWF, SCF, and TPA are determined by using FTIR and XRD. FTIR peak values are 1684 cm-1, 1574 cm-1, 1512 cm-1, 1280 cm-1, and 1425 cm-1 that prove transformation of polyester to TPA. XRD peaks confirm polyester conversion to TPA, and the values are 17.4, 25.13, 28.12, 29.09, and 38.7. TGA, SEM, and EDX data showed the thermal stability, morphology, and elemental composition of TPA.